2019
DOI: 10.1007/s10597-019-00373-0
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative Competence and Practices of Mental Health Professionals with LGB clients: An Ibero-American Study

Abstract: There are not many studies about affirmative competence and practices among mental health professionals working with Lesbian, Gay, and/or Bisexual (LGB) clients. Thus, the objectives of this research are to assess the levels of affirmative competence and practices of professionals in Ibero-American countries. The sample consists of 630 mental health professionals from various countries whose ages range from 22 to 75 years old, with a mean age of 41.46 years. The study utilizes the following measures: a socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…LGB + cultural competence training allowed service provider to feel more confident and skilful in working with LGB consumers (Croghan et al, 2015;Eady et al, 2011;Foy et al, 2019;Gandy et al, 2013;Graham et al, 2012;Hughes et al, 2018;Israel et al, 2008;Kilicaslan & Petrakis, 2019;McNamara & Wilson, 2020;Moe & Sparkman, 2015;Pennay et al, 2018;Pereira et al, 2019;Rutherford et al, 2012). Providers who engaged in LGB + cultural competence training reported more positive attitudes towards LGB consumers, greater understanding of how the societal context of having a minority sexual orientation can affect LGB consumers, greater skills in working with LGB consumers, more visibly affirming practices and provider confidence in working with LGB consumers (Croghan et al, 2015;Graham et al, 2012;Hughes et al, 2018;Israel et al, 2008;Moe & Sparkman, 2015;Rutherford et al, 2012).…”
Section: Service Provider Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…LGB + cultural competence training allowed service provider to feel more confident and skilful in working with LGB consumers (Croghan et al, 2015;Eady et al, 2011;Foy et al, 2019;Gandy et al, 2013;Graham et al, 2012;Hughes et al, 2018;Israel et al, 2008;Kilicaslan & Petrakis, 2019;McNamara & Wilson, 2020;Moe & Sparkman, 2015;Pennay et al, 2018;Pereira et al, 2019;Rutherford et al, 2012). Providers who engaged in LGB + cultural competence training reported more positive attitudes towards LGB consumers, greater understanding of how the societal context of having a minority sexual orientation can affect LGB consumers, greater skills in working with LGB consumers, more visibly affirming practices and provider confidence in working with LGB consumers (Croghan et al, 2015;Graham et al, 2012;Hughes et al, 2018;Israel et al, 2008;Moe & Sparkman, 2015;Rutherford et al, 2012).…”
Section: Service Provider Skillsmentioning
confidence: 99%
“…Consumers wanted providers to explore their sexuality only when it was relevant to the consumer's distress. Consumers felt more accepted in openly LGB affirming services Pereira et al (2019).…”
mentioning
confidence: 99%
“…This has the potential to improve the therapeutic alliance and facilitate psychological well-being (Owen et al, 2011). Several studies have concluded that, in order to work effectively with LGBT patients, therapists must feel comfortable with their own sexual identities and be ready to examine their beliefs, feelings, and prejudices, comfort or discomfort with the patients, cultural differences, and knowledge about how these aspects can affect the therapist-patient relationship (American Psychological Association, 2012Pereira et al, 2019).…”
Section: Therapists' Identity and Academic Trainingmentioning
confidence: 99%
“…LGBT topics and the use of the practical therapeutic skills mentioned above (Alessi et al, 2015;Boroughs et al, 2015;O'Shaughnessy and Speir, 2018;Pereira et al, 2019).…”
Section: Therapists' Identity and Academic Trainingmentioning
confidence: 99%
See 1 more Smart Citation